Penerapan WEMA dalam Peramalan Data IHSG - Seng Hansun (Ultimatics : Jurnal Teknik Informatika, 2013)
One of the most popular technical indicator used in time series analysis for predicting future data is the Moving Average method. During its’ development, many variation and implementation have been made by researchers, one of them is the Weighted Exponential Moving Average (WEMA) which is introduced by Hansun.In this paper, we will try to implement the WEMA method on one of stock market change indicator in Indonesia, i.e. the Jakarta Stock Exchange (JKSE) composite index data. The research is continued by calculating the accuracy and robustness of WEMA method, using MSE and MAPE criteria. The result shows that the WEMA method can be used to predict JKSE data and it’s quite accurate. Kata kunci—time series analysis, JKSE, moving average, WEMA